Zonation of bacterioplankton communities along aging upwelled water in the northern Benguela upwelling - Bergen, Benjamin; Herlemann, Daniel P. R.; Jürgens, Klaus (Frontiers in Microbiology, 2015)
Upwelling areas are shaped by enhanced primary production in surface waters, accompanied by a well-investigated planktonic succession. Although bacteria play an important role in biogeochemical cycles of upwelling systems, little is known about bacterial community composition and its development during upwelling events. The aim of this study was to investigate the succession of bacterial assemblages in aging upwelled water of the Benguela upwelling from coastal to offshore sites. Water from the upper mixed layer at 12 stations was sampled along two transects from the origin of the upwelling to a distance of 220 km. 16S rRNA gene amplicon sequencing was then used in a bacterial diversity analysis and major bacterial taxa were quantified by catalyzed reporter deposition-fluorescence in situ hybridization (CARD-FISH). Additionally, bacterial cell numbers and bacterial production were assessed . Community statistical analysis revealed a reproducible zonation along the two transects, with four clusters of significantly different microbial assemblages. Clustering was mainly driven by phytoplankton composition and abundance. Similar to the temporal succession that occurs during phytoplankton blooms in temperate coastal waters, operational taxonomic units (OTUs) affiliated with Bacteroidetes and Gammaproteobacteria were dominant during algal blooming whereas "Pelagibacterales" were highly abundant in regions with low algal abundance. The most dominant heterotrophic OTU (9% of all reads) was affiliated with "Pelagibacterales" and showed a strong negative correlation with phytoplankton. By contrast, the second most abundant heterotrophic OTU (6% of all reads) was affiliated with the phylum Verrucomicrobia and correlated positively with phytoplankton. Together with the close relation of bacterial production and phytoplankton abundance, our results showed that bacterial community dynamics is strongly driven by the development and composition of the phytoplankton community.